2021
DOI: 10.1002/rmb2.12380
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian tissue grafting: Lessons learnt from our experience with 55 grafts

Abstract: Purpose Uncertainties remain regarding the clinical efficacy of ovarian tissue cryopreservation and grafting. We report a retrospective analysis of reproductive outcomes and lessons learnt following 55 ovarian tissue transplant procedures at our center from 2006 to 2019. Methods We analyzed variables related to graft success such as tissue volume, follicular density, total follicular volume, and age on the duration of graft function. Results Follicular density and total follicular volume correlate positively w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…This result is supported by a report that primordial follicles are dormant and not vulnerable to chemotherapy 7 . These results suggest that OTC in children who have not yet menstruated is not inferior to OTC in adulthood, and the duration of ovarian function after OTT correlates positively with primordial follicle density 38 …”
Section: Discussionsupporting
confidence: 80%
“…This result is supported by a report that primordial follicles are dormant and not vulnerable to chemotherapy 7 . These results suggest that OTC in children who have not yet menstruated is not inferior to OTC in adulthood, and the duration of ovarian function after OTT correlates positively with primordial follicle density 38 …”
Section: Discussionsupporting
confidence: 80%
“…The Royal Women’s Hospital in Victoria, Australia also reported processing ovarian tissue into multiple different sizes ( 1 ): strips: 5 x 1 ( 2 ), squares: 5 x 5 ( 3 ), fragments: 2 x 2, 3 x 3, 4 x 3 mm 2 ( Table 2 ). Over 40 participants at this site had ovarian tissue processed into squares at the mean age of 26 (range 17.8 – 40.7), these participants had wide range of diagnoses ( 79 ). Also at this site 17 participants that had a mean age of 27.4 (range 17.8 – 35.9) at OTC had their ovarian tissue processed and cryopreserved into 5 x 1 mm 2 strips ( 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies were included for OTC (2 prospective ( Oktay and Oktem, 2010 ; Diaz-Garcia et al , 2018 ) and 13 retrospective ( Imbert et al , 2014 ; Meirow et al , 2016 ; Lambertini et al , 2018 ; Silber et al , 2018 ; Liebenthron et al , 2019 ; Poirot et al , 2019 ; Pretalli et al , 2019 ; Dueholm Hjorth et al , 2020 ; Marklund et al , 2020 ; Dolmans et al , 2021 ; Karavani et al , 2021 ; Rozen et al , 2021 ; Vatel et al , 2021 )). Seven studies reported orthotopic transplantation ( Meirow et al , 2016 ; Lambertini et al , 2018 ; Silber et al , 2018 ; Liebenthron et al , 2019 ; Pretalli et al , 2019 ; Dueholm Hjorth et al , 2020 ; Rozen et al , 2021 ), one reported heterotopic transplantation, four reported both ( Imbert et al , 2014 ; Poirot et al , 2019 ; Dolmans et al , 2021 ; Vatel et al , 2021 ) and three did not provide this information ( Diaz-Garcia et al , 2018 ; Marklund et al , 2020 ; Karavani et al , 2021 ). The time between OTT and first menstruation varied from 3.9 to 94.3 months.…”
Section: Ovarian Tissue Cryopreservationmentioning
confidence: 99%